2021
DOI: 10.1371/journal.pone.0249083
|View full text |Cite
|
Sign up to set email alerts
|

Birth preparedness and complication readiness practice and associated factors among pregnant women in Northwest Ethiopia: 2018

Abstract: Background Birth-preparedness and complication readiness is a comprehensive strategy aimed at promoting the timely utilization of skilled maternal and neonatal health care. Pregnancy-related complications both on the mother and the newborn could be largely alleviated if there is a well-consolidated birth preparedness and complication readiness plan developed during pregnancy and implemented at the time of delivery. Objective To determine the prevalence of birth preparedness and complication readiness practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…Debelie et al . [ 22 ] conducted a study on 1620 pregnant women found that prevalence of BPCR plan during pregnancy and the practice at the time of delivery were 66.1% and 73.5%, respectively. Only 15% were able to tell at least three of the five basic components of BPACR in study done by Saaka et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Debelie et al . [ 22 ] conducted a study on 1620 pregnant women found that prevalence of BPCR plan during pregnancy and the practice at the time of delivery were 66.1% and 73.5%, respectively. Only 15% were able to tell at least three of the five basic components of BPACR in study done by Saaka et al .…”
Section: Discussionmentioning
confidence: 99%
“…Debelie et al . [ 22 ] stated that frequency of ANC visits, larger number of family in the household, highest wealth asset, multigravidity, husband involvement in decision making, counseled on BPCR were found to be significantly associated with BPCR practice. Findings of these studies are quite similar to present study.…”
Section: Discussionmentioning
confidence: 99%
“…These issues could turn the pregnancy into a high-risk pregnancy. Obstetrical complications if there is a well-coordinated birth readiness and complication readiness plan created throughout pregnancy and put into practice at the time of delivery, both the mother and the newborn could be greatly reduced (Debbie et al, 2018). Involving male partners in antenatal care is important in improving positive maternal and newborn health outcomes.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Birth preparedness and complication readiness (BPCR) is the way toward making arrangements for normal delivery and anticipating activities required in emergency cases. It assists to ensure that women can arrive at skilled delivery care when labor begins and diminish postponement to look for care and to arrive at health care facilities that occur when women experience obstetric complications (3) .…”
Section: Introductionmentioning
confidence: 99%